Expression profile of p63 in 127 patients with laryngeal squamous cell carcinoma - Borba, M. (2010)
Objectives: To evaluate p63 expression in laryngeal squamous cell carcinoma and its prognostic significance. Methods: p63 expression was examined by immunohistochemistry and scored in 127 patients with laryngeal squamous cell carcinomas. Results: Sixty-two cases had scored 3, sixty had scored 2, four had scored 1 and one case did not show any expression (48.8, 47.2, 3.1 and 0.8%, respectively). Overall survival was 73.9% at 24 months and 59.5% at 60 months. The disease-free survival was 77.2 and 75.1%, and the disease-specific survival was 79 and 67% at 24 and 60 months, respectively. Uni- and multivariate analysis identified that decreased immunoexpression of protein p63 was a statistically significant factor for the risk of recurrence and death by cancer. Conclusions: p63 expression was highly prevalent in laryngeal squamous cell carcinomas, and its underexpression was correlated with a worse prognosis. Copyright © 2010 S. Karger AG, Basel.